CUMULUS AND STRATUS CLOUDS MICROSTRUCTURE (Perner's Contacts, 2011)
Clouds are the most visible elements of the sky and significantly contribute to the weather we experience every day. Clouds play an important role in the global energy and water budgets and affect the climate of the Earth. The presence of clouds affects the radiation balance of the region, the temperature of the air and exposed surfaces. Cloud formation requires moisture, aerosol particles and a process of cooling the air. The properties of many minute particles, that make up the cloud, characterize its microstructure. The special flight laboratory of University of Žilina presents unique device for obtaining information especially concerning the cloudy formation (base and upper-level cloudiness, state of matter, visibility in particular cloud types), turbulence, icing and concentration of the environmental gases and short-waves and long-waves radiation as well. This laboratory is a part of project „Centre of Excellence for Air Transport“ ITMS 26220120065 and will be irreplaceable source of meteorological information within the airport area and equally along chosen flight route.